(untitled) (Journal of Food and Dietetics Research, 2025)
Objectives: Lepidium sativum L. (Garden Cress) is an herb of Brassicaceae family growing in warm climates. The seeds contain mucilaginous compounds that are known to have bioactive properties. In the present investigation, extraction of Lepidiumsativum L. seed mucilage was followed by preliminary screening for carbohydrates, protein, mucilage, and qualitative and quantitative assessment of phytochemicals viz. total phenols, total flavonoids and tannin content. The extracted mucilage was also subjected to FT-IR analysis. Methods: Extraction of seeds of L.sativum was performed and it is dried at 60⁰C for 6-8 hrs, followed by qualitative tests for carbohydrates, protein, mucilage and phytochemicals. The total phenols were estimated using Folin Ciocalteu method, total flavonoids using Aluminium chloride method and tannin content using Folin Denis method. The FT-IR spectra was obtained using the KBr-pellet technique. Results: The screening tests showed the presence of carbohydrates, amino acids and phytochemicals. The total phenolic, flavonoid and tannin content estimated was 109±1.8 mgGAE/100 g, 96.2 ± 2.4 mgQE/100 g and 87.4 ± 3.2 mgTAE/100 g respectively. The FT-IR spectra of mucilage showed the presence of hydroxyl groups, carbonyl groups and confirm the region for carbohydrates and protein. Conclusion: The phytochemical composition of garden cress seed mucilage can be a vital element in food functions which could strengthen the gum structure, improve food and gum interactions and enhance the shelf- life stability. In conclusion, garden cress mucilage appears to have distinct health benefits with added advantages as efficient additive in food products.